Time-clustering of wave storms in the Mediterranean Sea - Besio, Giovanni; Briganti, Riccardo; Romano, Alessandro; Mentaschi, Lorenzo; De Girolamo, Paolo (European Geosciences Union, 2017)
In this contribution we identify storm time-clustering in the Mediterranean Sea through a comprehensive analysis of the Allan Factor. This parameter is evaluated from long time series of wave height provided by oceanographic buoy measurements and hindcast re-analysis of the whole basin, spanning the period 1979-2014 and characterized by a horizontal resolution of about 0.1 degree in longitude and latitude and a temporal sampling of one hour (Mentaschi et al., 2015). The nature of the processes highlighted by the AF and the spatial distribution of the parameter are both investigated. Results reveal that the Allan Factor follows different curves at two distinct time scales. The range of time scales between 12 hrs to 50 days is characterised by a departure from the Poisson distribution. For timescales above 50 days, a cyclic Poisson process is identified. The spatial distribution of the Allan Factor reveals that the clustering at smaller time scales is present in the North-West of the Mediterranean, while seasonality is observed in the whole basin. This analysis is believed to be important to assess the local increased flood and coastal erosion risks due to storm clustering.